Machine milkability of East Friesian and Lacaune dairy sheep - MAKOVICKÝ, PAVOL; MARGETÍN, MILAN; MAKOVICKÝ, PETER; NAGY, MELINDA (The Indian Journal of Animal Sciences, 2019)
Udder morphology and milking characteristics are one of the factors determining milkability in dairy ewes. Udder morphology traits were measured and subjectively assessed by the use of linear scores in 150 ewes of Lacaune (LC) and East Friesian (EF) dairy breeds. Linear scores were assessed for udder depth, cistern depth, teat placement, teat length, udder attachment, udder cleft, and udder shape. Nine traits characterized by milk production and milkability were analyzed in machine milking conditions (150 measurements). Analysis of variance was done by the GLM procedure of SAS statistical package. Extraordinary great variability in all traits of linear udder evaluation was detected, as well as in traits connected with milk production and milkability. The obtained results suggest that LC breed has better milkability parameters than EF breed. The differences in milk production and analysed parameters of milkability were too large between the individual flocks.